2022
DOI: 10.1128/jvi.01695-21
|View full text |Cite
|
Sign up to set email alerts
|

The PERK/PKR-eIF2α Pathway Negatively Regulates Porcine Hemagglutinating Encephalomyelitis Virus Replication by Attenuating Global Protein Translation and Facilitating Stress Granule Formation

Abstract: The replication of coronaviruses, including severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV) and the recently emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is closely associated with the endoplasmic reticulum (ER) of infected cells. The unfolded protein response (UPR), which is mediated by ER stress (ERS), is a typical outcome in coronavirus-infected cells and is closely associated with the characteristics of coronaviruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…It is likely that the antibodies used in our experiments did not efficiently recognize the amino-terminus of porcine ATF6. Similar cases have been described in previous reports ( Echavarria-Consuegra et al, 2021 , Shi et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is likely that the antibodies used in our experiments did not efficiently recognize the amino-terminus of porcine ATF6. Similar cases have been described in previous reports ( Echavarria-Consuegra et al, 2021 , Shi et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
“…For example, Porcine epidemic diarrhea virus (PEDV) and TGEV infection induce ERS and promote GRP78 protein expression ( Sun et al, 2021 , Xue et al, 2018 ). Porcine hemagglutinating encephalomyelitis virus (PHEV) infection activates all three UPR arms and increases GRP78 expression at both the mRNA and protein levels ( Shi et al, 2022 ). PRRSV targets the UPR master regulator GRP78 for degradation despite inducing an increase in its mRNA levels in a time-dependent manner ( Gao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) is an essential organelle in eukaryotes that is mainly responsible for protein assembly, modification, folding, calcium storage, and lipid synthesis ( Metcalf et al., 2020 ). Studies have shown that when viruses interact with cells, large amounts of viral proteins accumulate in the ER lumen, which perturbs the homeostasis and function of the ER, triggering the UPR ( Prasad and Greber, 2021 ; Shaban et al., 2021 ; Shi et al., 2021 ). Regulation of the ERS on UPR signals is mainly dependent on three pathways (ATF6, PERK, and IRE1).…”
Section: Discussionmentioning
confidence: 99%
“…The TEM analysis was performed as previously described [ 32 ]. Briefly, PHEV-infected mouse brain samples were collected, fixed with 2.5% glutaraldehyde for 24 h, and then postfixed with 1% osmium tetroxide for 2 h. After dehydration using a graded ethanol series, the specimens were embedded in Renlam resin.…”
Section: Methodsmentioning
confidence: 99%
“…Neurodegenerative changes, such as axonal dysplasia, unstable dendritic spine formation, and irregular swelling and disconnection in neurites, are linked to the Ulk1-TrkA-NGF-Rab5 signaling pathway [29,30]. Furthermore, PHEV-induced neurodegeneration is related to lysosome dysfunction and endoplasmic reticulum (ER) stress [31][32][33], similar to the pathogenesis of human neurodegenerative diseases such as Parkinson's disease, frontotemporal degeneration and neuronal lipofuscinosis, indicating that PHEV might be a useful model virus to study the mechanisms of human neurodegenerative disease [33].…”
Section: Introductionmentioning
confidence: 99%